2009
DOI: 10.1109/jphot.2009.2027441
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence-Induced Trains of High-Rate Pulses in a Mode-Locked Fiber Laser

Abstract: The output of a mode-locked erbium-doped ring fiber laser incorporating a section of a polarization-maintaining (PM) fiber is investigated in both numerical simulations and experiments. With proper inline polarization control, the laser can be set to emit a train of pulses, separated by the differential group delay of the PM section. Repetition rates as high as 500 GHz are experimentally observed. The results provide an added insight into the role of birefringence in mode-locked lasers based on nonlinear polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The generation of the rogue-like wave in DOF can be controlled by adjusting the modulation period and the temporal separation between the peak of the initial pulses. Mode-locked lasers can demonstrate generation packets of closely spaced pulses [46][47][48][49]. Soliton fusion can be used for converting pulse packets into new pulses with increased peak power.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The generation of the rogue-like wave in DOF can be controlled by adjusting the modulation period and the temporal separation between the peak of the initial pulses. Mode-locked lasers can demonstrate generation packets of closely spaced pulses [46][47][48][49]. Soliton fusion can be used for converting pulse packets into new pulses with increased peak power.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Then, an HRR pulse train is finally formed with a repetition rate defined by the free spectral range (FSR) of the comb filter. During the past decades, various schemes based on DFWM have been reported, such as sampled fiber Bragg grating [ 18 , 20 , 21 , 22 ], F-P filters [ 23 , 24 ], Mach–Zehnder interferometers [ 25 , 26 ], Lyot filters [ 27 , 28 ], programmable optical processors [ 29 , 30 ], and microring resonators [ 31 , 32 ]. In particular, J. Schröder et al experimentally obtained up to a 20 nm wavelength tunability by incorporating a programmable optical processor in the cavity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Coen and Haeltermann used a CW pump for the same observation [11]. Ring cavities are promising for producing pulse trains with rates exceeding 500 GHz [12]. More recently, numerous studies have demonstrated the potential of microring resonators for producing frequency combs [13,14].…”
Section: Introductionmentioning
confidence: 99%